Irrigation Procedure And The Effect Of Mineral Fertilizer Norms On Autumn Rye Grain Yield - Abdurahmonov Sodiqjon Obidovich, Abdullaev Ismoiljon Ibrahimjonovich, Abdurahmonov Saydullokhon Jurahonovich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the conditions of light gray soils of Andijan region studied the norms of mineral fertilizers and the requirements for irrigation procedures in the cultivation of high-quality grain from autumn rye. The obtained data show that pre-irrigation soil moisture is irrigated at 70–70–60% relative to the ChDNS, and mineral fertilizers are applied. N150P75K120 and N200P100K160 When applying the norms of kg / ha, in addition to the control option 6.7–10.5 ts / ha, pre-irrigation soil moisture is irrigated at 70–80–70% relative to the ChDNS, mineral fertilizers N150P75K120 ва N200P100K160 When applying the norms of kg / ha, an additional grain yield of 8.0–12.2 ts / ha was obtained compared to the control variant.